Does Reading Increase the Younger Generation's Intention to Use Islamic Non-Bank Financial Products? - Windari Windari; Ali Hardana; Muhammad Wandisyah R Hutagalung; Sry Lestari; Fitrah Fitrah (Al-Kharaj: Journal of Islamic Economic and Business, 2023)
Islamic financial institutions have traditionally been dominated by the banking sector. Non-Bank Financial Institutions (NBFIs) actually offer options to meet the various financial needs of the general people. A highly potential target market for Islamic Non-Bank Financial Institutions is the younger Muslim population. This study aims to investigate the potential impact of literacy on young Muslims' inclination to use products offered by non-bank financial institutions. This study uses a quantitative approach using simple linear regression analysis on 138 Muslim youth in North Sumatra. The results of the study demonstrate that the intentions of the younger generation of Muslims to utilize products from Islamic Non-Bank Financial Institutions are positively and significantly influenced by literacy. The official and informal forms of education and socialization play a significant role in increasing the literacy rate of the younger Muslim generations.